Ultra-Thick Organic Pigment Layer Up to 10 μm Activated by Crystallization in Organic Photovoltaic Cells - Katayama, Mikimasa; Kaji, Toshihiko; Nakao, Satoru; Hiramoto, Masahiro (Frontiers in Energy Research, 2020)
Organic optoelectronic devices tend to have limited thickness. Organic light emitting diodes (OLED) and organic photovoltaic cells (OPV) made of organic pigments are typically with thickness of a few or a few tens of nanometers. Thickness of organic photovoltaic cells made with polymers exceeds them typically up to the order of a few hundred nanometers but still necessarily co-optimized with respect to light absorption and charge transport. Here, we demonstrate that crystallization made a 10-µm-thick pigment layer active in a photovoltaic cell, using a prototypical pair of pigments, phthalocyanine and fullerene. It is proved that crystalline pigment layer with a thickness much greater than what is needed for optical optimization can be utilized for organic optoelectronic devices and that organic optoelectronic devices have potentiality to relief their design from co-optimization of optics and charge transport.